THE ACCURACY OF RISK SCORES IN PREDICTING PRETERM BIRTH : A SYSTEMATIC REVIEW - Porman Surtana Siahaan, Hatsari Marintan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Preterm birth (PTB) is a leading cause of infant illness and death. PTB is spontaneous in two-thirds of instances.  SPTB is problematic because it has several causes. If SPTB has occurred before, it will likely happen again. PTB is hard to forecast because the scenario is varied and there are many causes and risk factors. Risk score accuracy in predicting premature birth is discussed. The aim: This study demonstrated the accurateness of risk score predictions for premature birth. Methods: This study demonstrated that it met all of the requirements by comparing itself to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. As a result, the specialists were able to ensure that the study was as up to date as possible. Publications published between 2013 and 2023 were considered for this search strategy. This was accomplished using a variety of online reference sources, including Pubmed and SagePub. It was chosen not to include review pieces, previously published works, or works that were just partially completed. Result: In the PubMed database, the results of our search brought up 415 articles and SagePub 366 articles. The results of the search conducted for the last year of 2013 yielded a total 56 articles for PubMed and 49 articles from SagePub. In the end, we compiled a total of 10 papers. Conclusion: Preterm birth has been associated to a short cervix, a maternal age over 35, a maternal body mass index above 25, smoking, and concomitant risk factors like hypertension and diabetes.